Writing on Gaps and around the Reproduction of Exclusion - Piiroinen, Eeti (Taideyliopiston Kuvataideakatemia, 2024)
The artistic part of my thesis is the video essay Gaps, or; Reproducing Exclusion as exhibited as part of the annual MFA Degree Show Kuvan Kevät at the Academy of Fine Arts, University of the Arts Helsinki, in the Spring 2024. In an effort to accommodate for accessibility the artwork could be found in three locations throughout the exhibition. The almost 61-minute piece begins by drawing attention to gaps as institutional devices that reproduce exclusion (following Sara Ahmed): how there’s often a gap between the portrayals institutions promote about themselves and how those institutions are experienced by people who come into contact with them. Combining critical theory with narratives of marginalization and discrimination gathered through research interviews, the essay film lays out an inclusive understanding of the ways Whiteness is actively reproduced in our everyday environments. As a case study, the work introduces the context, the outward policy vs. actual policy, and the exclusionary culture and discrimination experienced by marginalized students within the Academy of Fine Arts. In the written part of my thesis, I draw the themes together under the concept of gaps – how gaps are strategically enforced to separate words from action to separate acknowledgements or records of discrimination or injustice from functional, operative practice that would correct injustices and end discrimination. Present-day power relations are reproduced through systemically renewed ignorance, refusal to engage in conversations about racial dynamics and convenient gaps in memories and knowledge that protect White people from guilt and moral judgements – like the structurally supported ignorance of the realities of settler colonialism. In the written part of my artistic thesis, I also describe the different components of the artwork and its installation. I reflect on the choices made regarding its form, content and public presentation. I elaborate on the theoretical inspirations and concepts behind the piece. I make an effort to create connections between Gaps,... and other works of contemporary art, and I examine the importance of theory in my artistic practice.
Keywords: Ableismi; kuvataide; taide; taiteellinen työ; taiteellinen tutkimus; rasismi; taidekorkeakoulut; yliopistot; fi=tila-aikataiteet|sv=tid- och rumkonst|en=Time and Space Arts|